Makassar City Climate Change Handling Policy - Aswar Annas; Resky Amalia P (Universitas Muhammadiyah Tangerang, 2024)
The urgency of climate change is now crucial. Climate change is not only an environmental problem but also threatens the survival of urban communities, affects urban spatial planning, and encourages government initiatives to increase public capacity and integrated social services. This study aims to identify and analyze the implementation of policies and handling of climate change by the government of Makassar City. This study uses qualitative data sources, namely statements from informants and local action plan documents for climate change adaptation and disaster risk reduction. Data collection through interviews and relevant literature review. The study results show that the climate change countermeasures policies implemented include; adding green open spaces, clean water management, rehabilitation and normalization of canals, mitigation through planting mangroves, developing aquaculture to empower island communities, and socializing strengthening climate change regulations. Other policies were carried out, including the ecological dimensions of forming strategic areas and cultivation, the social dimension of public capacity building and integrated social services, technical dimensions of the development of urban spatial pattern structures.Urgensi perubahan iklim saat ini menjadi krusial. Perubahan iklim bukan hanya mengenai masalah lingkungan, tetapi juga mengancam ketahanan hidup masyarakat kota, memengaruhi penataan ruang kota, dan mendorong inisiatif pemerintah untuk meningkatkan kapasitas publik dan layanan sosial terpadu. Penelitian ini bertujuan untuk mengetahui dan menganalisis pelaksanaan kebijakan dan penanganan perubahan iklim yang dilakukan pemerintah Kota Makassar. Pendekatan penelitian menggunakan kualitatif, sumber data yaitu pernyataan yang berasal dari informan, dan dokuman rencana aksi daerah adaptasi perubahan iklim dan pengurangan risiko bencana. Pengumpulan data melalui wawancara dan telaah literatur relevan. Hasil penelitian menunjukkan bahwa kebijakan penangan perubahan iklim dilakukan, meliputi; penambahan ruang terbuka hijau, pengelolaan air bersih, rehabilisasi dan normalisasi kanal, mitigasi melalui penanaman mangrove, pengembangan budidaya perikanan pemberdayaan masyarakat pulau, dan sosialisasi penguatan aturan perubahan iklim. Kebijakan lain dilakukan, yaitu; dimensi ekologi pembentukan kawasan strategi dan budidaya, dimensi sosial peningkatan kapasitas publik dan layanan sosial terpadu, dan dimensi teknis pengembangan struktur pola ruang perkotaan.